Peran Kepala Madrasah dalam Meningkatkan Manajemen Mutu Pendidikan di MTsN 2 Jombang - Moh. Hilmi Santosa; M. Aliyul Wafa (Lembaga Yasin AlSys, 2025)
This study examines the strategic role of the principal in enhancing quality management in education at MTsN 2 Jombang, focusing on five key dimensions: manager, administrator, supervisor, leader, and motivator. A qualitative descriptive design was employed, with data collected through semi-structured interviews, participatory observations, and document studies. Data analysis followed the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that managerial roles are carried out systematically through data-based planning, organizing, implementation, supervision, and evaluation of work programs. In administrative aspects, the principal manages documents and supporting facilities in an orderly and transparent manner. As a supervisor, the principal implements academic supervision to improve teachers’ competencies. Leadership is exercised in a transformational manner, emphasizing role modeling, open communication, and a strong vision. The role of motivator is demonstrated through the provision of appreciation and reinforcement of teachers’ and educational staff’s work morale. These findings affirm that the principal’s leadership significantly contributes to shaping a professional, quality-oriented work culture in the madrasah.